Depression, Environmental Reward, Coping Motives and Alcohol Consumption During the COVID-19 Pandemic - McPhee, Matthew D.; Keough, Matthew T.; Rundle, Samantha; Heath, Laura M.; Wardell, Jeffrey D.; Hendershot, Christian S. (Frontiers in Psychiatry, 2020)
Background. Increases in the incidence of psychological distress and alcohol use during the COVID-19 pandemic have been predicted. Environmental reward and self-medication theories suggest that increased distress and greater social/environmental constraints during COVID-19 could result in increases in depression and drinking to cope with negative affect. The current study had two goals: (1) to clarify the presence and direction of changes in alcohol use and related outcomes after the introduction of COVID-19 social distancing requirements, and; (2) to test hypothesized mediation models to explain individual differences in alcohol use during the early weeks of the COVID-19 pandemic. Methods. Participants (n = 1127) were U.S. residents recruited for participation in an online survey. The survey included questions assessing environmental reward, depression, COVID-19-related distress, drinking motives, and alcohol use outcomes (alcohol use; drinking motives; alcohol demand, and solitary drinking). Outcomes were assessed for two timeframes: the 30 days prior to state-mandated social distancing (‘pre-social-distancing’), and the 30 days after the start of state-mandated social distancing (‘post-social-distancing’). Results. Depression severity, coping motives, and frequency of solitary drinking were significantly greater post-social-distancing relative to pre-social-distancing. Conversely, environmental reward and other drinking motives (social, enhancement, and conformity) were significantly lower post-social distancing compared to pre-social-distancing. Time spent drinking and frequency of binge drinking were greater post-social-distancing compared to pre-social-distancing, whereas typical alcohol quantity/frequency were not significantly different between timeframes. Indices of alcohol demand were variable with regard to change. Mediation analyses suggested a significant indirect effects of reduced environmental reward with drinking quantity/frequency via increased depressive symptoms and coping motives, and a significant indirect effect of COVID-related distress with alcohol quantity/frequency via coping motives for drinking. Discussion. Results provide early evidence regarding the relation of psychological distress with alcohol consumption and coping motives during the early weeks of the COVID-19 pandemic. Moreover, results largely converged with predictions from self-medication and environmental reinforcement theories. Future research will be needed to study prospective associations among these outcomes.